INVESTIGATION OF THE GEOTHERMAL RESOURCE POTENTIAL USING GEOELECTRICAL METHOD WITH THE WENNER CONFIGURATION: A CASE STUDY IN LEBONG REGENCY, INDONESIA - Raihana, Hana; Nazli, Khairun; Suhendra, Suhendra; Refrizon, Refrizon; Halauddin, Halauddin (Indonesian Physical Review, 2023)
In geothermal reservoirs, hydrothermal distribution is significant. The most widely utilized geothermal reservoirs to date are those of hydrothermal systems, which are geothermal systems where the reservoir contains steam, water, or a mixture of both, depending on the pressure and temperature of the reservoir. One of geophysical method that is enough to map subsurface conditions to determine the hydrothermal distribution is the 2-Dimensional Geoelectric method using the Wenner configuration. This method aims to study the variation of rock resistivity below the earth's surface, resulting in a two-dimensional profile of the subsurface resistivity model used to describe the layered subsurface resistivity structure. The results are in the form of 2-Dimensional modeling of the distribution of hydrothermal manifestations with data processing using pyGIMLI (Python Library for Inversion and Modeling in Geophysics) software. In the study area Â Pungguk Pedaro Village, Bingin Kuning District, Lebong Regency, the Hulusimpang Formation has a high alteration intensity, as evidenced by the weathering in rocks and the micrographic appearance. The types of stones found in this research area include andesite rocks, including sandy gravel, volcanic breccia, tuff, andesite, basalt, basalt-andesite sand, silty sand, and clay. Or rocks derived from acidic magma.